Socio-cognitive and Professional Practice Perspectives on Chairperson Statements - Yee, Vivian Chiew Ling; Cheong, Cecilia Yin Mei (Journal of Modern Languages, 2022)
The study establishes the Malaysian chairperson statements from the socio-cognitive and professional practice perspectives. It identifies the move structure of 53 chairperson statements and metadiscourse strategies based on questionnaire and interview responses collected from 39 investors and 3 professional members. Three informational moves are used to assist investment decisions while seven non-informational moves are intended to build good image and good will, and to ensure compliance to requirements. Self-mentions, attitude markers, frame markers and transitions are also used to affectively realise the promotional and interpersonal moves. The chairperson statements are interdiscursively informational, promotional, and public relational. This research highlights pedagogy implications for English for Professional Communication (EPC) programmes, and recommendations for future studies.